Evaluation of Fixed Asset Presentation Based on Government Accounting Standards (SAP) at Regional General Hospitals (RSUD) Bahteramas, Southeast Sulawesi Province - Wa Ode Retno Selvita; Husin; Yuli Lestari Labangu (Takaza Innovatix Labs Ltd., 2025)
This study aims to evaluate the presentation of fixed assets at Bahteramas Regional General Hospital (RSUD) Southeast Sulawesi Province based on Government Accounting Standards (SAP). Fixed assets are one of the key components in local government financial statements because they have significant material value and influence the presentation of the balance sheet and operational reports. This research employs a descriptive analysis approach with a case study method. Data were collected through documentation of RSUD Bahteramas' financial reports, interviews with relevant parties, and a literature review on government accounting regulations, particularly PSAP No. 07 on Fixed Asset Accounting. The findings indicate that the presentation of fixed assets at RSUD Bahteramas has been referred to SAP provisions, both in terms of recognition, measurement, and presentation in financial statements. Fixed assets are recognized when received and ready for use, measured based on acquisition cost and fair value (especially for grant assets), and depreciated using the straight-line method according to the useful life of the assets.